국내 억새 유전자원 수집 후 형태 및 생육 특성 변화 - 이지은(Ji-Eun Lee); 문윤호(Youn-Ho Moon); 유경단(Gyeong-Dan Yu); 최인성(In-Seong Choi); 차영록(Young-Lok Cha); 김광수(Kwang-Soo Kim); 송연상(Yeon-Sang Song) (Weed & turfgrass science, 2018)
Miscanthus has been considered as the most promising bioenergy crop for lignocellulosic biomass production. In Korea, M. sacchariflorus and M. sinensis can be found easily in all regions. It is a great advantage to utilize as important species with respect to genetic and cross-breeding programs materials for creation of novel hybrids. For successful breeding programs, it is important to precisely understand the variability of morphological and growth characteristics among Miscanthus species as breeding parent materials. In this study, morphological and growth characteristics were observed in 960 germplasms of two Miscanthus species (M. sacchariflorus and M. sinensis) for growing seasons over three years. Due to the inherent characteristics of these species, the germplasm of M. sacchariflorus among the collected germplasm were reduced in plant height than in the collection area. In M. sinensis, the plant height of germplasm collected mainly from Jeju-do increased more than those collected from collection area. Sixty-one of the collected 960 germplasms were selected and investigated to the morphological characteristics. Based on the investigated morphological data, the phylogenic tree was developed. As the results, it was confirmed that there exist germplasm in which the characteristics of M. sacchariflorus and M. sinensis are mixed. This study of Miscanthus may provide an important information in order to expedite the introduction as breeding materials for creation of new hybrid.